Unravelling the Nation: Digital Contestations of Gendered Narratives in the Iranian Women, Life, Freedom Movement - Shamsi, Mitra (AoIR Selected Papers of Internet Research, 2026)
The Women, Life, Freedom (WLF) movement of 2022-2023 marked a historic shift in Iranian politics by centring women’s issues in public discourse. During and after the uprising, digital platforms became battlegrounds where competing political forces struggled to shape and control narratives around gender issues and national identity. In this context, the research examines how competing gendered narratives were constructed and contested on digital platforms, focusing on feminist activists’ media and discursive strategies in navigating and disrupting digital patriarchal nationalist narratives inside Iran and across the diaspora. Employing a multi-sited ethnographic approach, the study examines an archive of textual and visual materials published online using frame analysis to explore key gendered discussions and highlight how different political actors shaped, resisted, and reframed dominant gendered narratives. The analysis shows that pro-government forces and monarchists strategically deploy nationalist rhetoric centered on gender to shape and control narratives and legitimise their political positions. Within this contested space, feminist activists play a crucial role by appropriating affordances of digital spaces to challenge dominant narratives, constructing counter-narratives that reframe women’s issues and gendered debates. Digital platforms in the Iranian context have emerged as contested and paradoxical spaces, simultaneously enabling mobilisation for political transformation and reinforcing nationalist framing as mechanisms of discursive control.